Rubber band engineer : from a slingshot rifle to a mousetrap catapult, build 10 guerrilla gadgets from household hardware /: from a slingshot rifle to a mousetrap catapult, build 10 guerrilla gadgets from household hardware. (2019) - Akiyama, Lance
No abstract available